2017
DOI: 10.1002/sim.7504
|View full text |Cite
|
Sign up to set email alerts
|

Type I error probability spending for post–market drug and vaccine safety surveillance with binomial data

Abstract: Type I error probability spending functions are commonly used for designing sequential analysis of binomial data in clinical trials, but it is also quickly emerging for near-continuous sequential analysis of post-market drug and vaccine safety surveillance. It is well known that, for clinical trials, when the null hypothesis is not rejected, it is still important to minimize the sample size. Unlike, in post-market drug and vaccine safety surveillance, that is not important. In post-market safety surveillance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…However, more recently, some results have shown that if the design criterion is expected time to signal, then a concave alpha spending function should be used instead. This is advocated, for example, in an earlier paper by Silva . That paper shows that usage of ρ = 0.5 favors near‐optimal expected time to signal when data follow a binomial distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recently, some results have shown that if the design criterion is expected time to signal, then a concave alpha spending function should be used instead. This is advocated, for example, in an earlier paper by Silva . That paper shows that usage of ρ = 0.5 favors near‐optimal expected time to signal when data follow a binomial distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Studies directed to identify suitable alpha spending shapes for postmarket safety surveillance are just emerging. Seminal works in this direction are the developments of Silva and Kulldorff, where the minimization of expected time to signal was taken as the key design criterion. Their findings suggest that, unlike clinical trials, the alpha spending should have a concave shape for postmarket safety surveillance applications for both Poisson and binomial data.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to begin testing earlier in the influenza season, there can be a substantial amount of noise in sequential testing when the outcome is rare, and there are alternative triggers and pathological mechanisms involved . Further investigation is needed to explore possible solutions including the use of an O'Brien‐Fleming threshold, a minimum number of events to signal, or a different alpha spending plan …”
Section: Discussionmentioning
confidence: 99%
“…23,24 Further investigation is needed to explore possible solutions including the use of an O'Brien-Fleming threshold, a minimum number of events to signal, or a different alpha spending plan. 21,25,26 USPRT's adjustment for both clinical and processing delay may be more suited to insurance claims databases as opposed to Influenza vaccines save lives and prevent many illnesses and their associated effects on morbidity, mortality, and economic losses. 30 Despite the possible risk of GBS due to the influenza vaccines, influenza infection seems to also be a relevant trigger for GBS, and thus, lowering the incidence of influenza by vaccination might protect against GBS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies devoted to explore suitable choices of ρ having the expected time to signal as the main design criteria are just emerging. An example is the work of Silva (2018) suggesting that values of ρ around 0.5 are appropriate choices if the design criterion is the minimization of the expected time to signal.…”
Section: Group Sequential Analysis: the Type I Error Probability Funcmentioning
confidence: 99%